2016
DOI: 10.1016/j.hrthm.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Small conductance calcium-activated potassium current and the mechanism of atrial arrhythmia in mice with dysfunctional melanocyte-like cells

Abstract: Background The melanin synthesis enzyme dopachrome tautomerase (Dct) regulates intracellular Ca2+ in melanocytes. Homozygous Dct knock out (Dct−/−) adult mice are vulnerable to atrial arrhythmias (AA). Objective To determine if apamin-sensitive small conductance Ca2+ activated K+ currents (IKAS) are upregulated in Dct−/− mice and contribute to AA. Methods Optical mapping was used to study the membrane potential of right atria (RA) in Langendorff perfused Dct−/− (N=9) and Dct+/− (N=9) mice. Results Apamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The first potential clinical implication is that ondansetron may be useful as an antiarrhythmic agent. Previous studies in animal models have shown that apamin is potentially useful in the management of electrical storm (7) and atrial fibrillation (6,24,26). However, because apamin is a neurotoxin, it cannot be used as a drug for humans.…”
Section: Discussionmentioning
confidence: 99%
“…The first potential clinical implication is that ondansetron may be useful as an antiarrhythmic agent. Previous studies in animal models have shown that apamin is potentially useful in the management of electrical storm (7) and atrial fibrillation (6,24,26). However, because apamin is a neurotoxin, it cannot be used as a drug for humans.…”
Section: Discussionmentioning
confidence: 99%
“…28 Enhanced L-type Ca 2+ current and aberrant ryanodine receptor type 2 regulation are among the dominant mechanisms responsible for cardiac arrhythmogenesis. 29, 30 Prior studies showed that SK currents are upregulated in pathogenic conditions while SK current blockade may be proarrhythmic, 10, 31 suggesting that SK current upregulation is a physiological response to reduced repolarization reserve and that SK current blockade might be arrhythmogenic in certain clinical conditions. 32 The data obtained in our present study suggest that mutant calmodulin impedes the activation of SK current, which may play a role in the arrhythmic phenotypes experienced by patients with calmodulin mutations.…”
Section: Discussionmentioning
confidence: 99%
“…HF‐related atrial arrhythmogenesis is characterized by decreased atrial K + currents, resulting in prolongation of atrial APD and AERP (Lugenbiel et al, 2017; Schmidt et al, 2017). Reduced K Ca channel expression and function in AF may contribute to this electrophysiological hallmark of AF/HF patients (Diness et al, 2010; Li et al, 2009; Ozgen et al, 2007; Qi et al, 2014; Skibsbye et al, 2014; Tsai et al, 2016; Zhang, Timofeyev, et al, 2014). Reversal of K Ca 2.1 channel remodeling could represent an individualized strategy for rhythm control in this specific AF patient entity.…”
Section: Discussionmentioning
confidence: 99%